Needs Analysis of English Teaching Materials for Vocational High School Students: Preparing for the World of Work - Fuadul Matin, Moh. (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
English for Specific Purposes (ESP) in vocational education plays a pivotal role in preparing students for professional communication in their future workplaces. However, many English materials used in Indonesian vocational high schools (SMK) still focus on general English, with limited relevance to the students’ vocational fields. This study aims to analyze the English material needs of SMK students to ensure alignment with the linguistic demands of the world of work especially in tourism. Using a qualitative descriptive method, interview to the students, literature-based analysis, the study identifies the gaps between current teaching materials and workplace communication needs. Findings reveal that English materials should emphasize job-related communication, technical vocabulary, and intercultural competence. The study suggests that English teachers and curriculum developers integrate authentic workplace tasks and collaborate with industry professionals to design effective, context-based learning materials.